Brain-Drain: Challenges and Opportunities in Nepal (SS Multidisciplinary Research Journal, 2025)
Brain drain, also referred to as brain gain, represents a global phenomenon and is a highly debated topic in today's world. It exerts adverse effects on developing countries, while yielding beneficial outcomes in developed nations. This article relies on secondary data sources, which have been collected from various published documents, and employs dependency and world system theory, particularly focusing on the unequal core–periphery dynamics. The discussion traces back to the Paleolithic era, elaborating on the out-of-Africa hypothesis, with significant occurrences noted between 1960 and 1970 AD. The primary focus of this article is the dual impacts of brain drain in Nepal. Annually, over seven hundred thousand individuals leave Nepal, with a significantly lower number of brains gain in comparison to the earlier trends. Factors such as inadequate infrastructure, insufficient quality education, limited job opportunities, poverty, corruption, and political instability have led to the migration of a majority of human resources from Nepal, resulting in detrimental effects on the social, economic, and cultural sectors in the country. Brain drain, also referred to as brain gain, represents a global phenomenon and is a highly debated topic in today's world. It exerts adverse effects on developing countries, while yielding beneficial outcomes in developed nations. This article relies on secondary data sources, which have been collected from various published documents, and employs dependency and world system theory, particularly focusing on the unequal core–periphery dynamics. The discussion traces back to the Paleolithic era, elaborating on the out-of-Africa hypothesis, with significant occurrences noted between 1960 and 1970 AD. The primary focus of this article is the dual impacts of brain drain in Nepal. Annually, over seven hundred thousand individuals leave Nepal, with a significantly lower number of brains gain in comparison to the earlier trends. Factors such as inadequate infrastructure, insufficient quality education, limited job opportunities, poverty, corruption, and political instability have led to the migration of a majority of human resources from Nepal, resulting in detrimental effects on the social, economic, and cultural sectors in the country.